Authority of the Indonesian Broadcasting Commission (KPI) Against Youtube and Netflix According to Law Number 32 of 2002 Regarding Broadcasting - Astria Yuli Satyarini Sukendar,; Amanda Raissa,; Tomy Michael, (Technium Social Sciences Journal, 2020)
Today there are a lot of developments in broadcast technology in Indonesia, educational and quality shows are an important need for everyone. That is because quality shows will form a quality society. Broadcast technology that is currently well-known and widely discussed and widely accessed by people in Indonesia is Youtube and Netflix, people who want to access videos and films will be spoiled with the convenience provided by this platform. But what is unfortunate from the existence of Youtube and Netflix is the vastness of shows that can be accessed by everyone and also children without any screening, supervision, and mastery of the Indonesian Censorship Institution first. For now, the government still cannot do anything in filtering shows that should not be broadcast on Youtube and Netflix, because in Law Number 32 of 2002 on Broadcasting it does not explicitly explain the authority of the Indonesian Broadcasting Commission in overseeing content on both platforms like Youtube and Netflix. Therefore, in this writing the author will highlight how the Government can take a position to filter out content that should not be displayed to the public in Indonesia as well as surveillance conducted on the Youtube and Netflix platforms. The method used in this writing is Juridical Empirical in which the writer looks at the facts that exist in society and mix and match with the rules and laws that exist and apply in Indonesia. The result of this writing is that there needs to be a change in the Broadcasting Law so that there is supervision and also restrictions on the content displayed on the digital platform.